Model Manajemen Sumberdaya Komunikasi untuk Penyuluhan Pertanian dalam Pelaksanaan Sistem Pertanian Terintegrasi di Provinsi Bali - I Dewa Putu Oka Suardi; Nyoman Parining; I Made Sukewijaya (Universitas Udayana, 2015)
Communication resource for extension of integrated agricultural systems program which includes: facilitators agents, farmers, messages, methods, and facilities/infrastructure is not well maintained premises. Communication effectiveness of integrated farming systems program is only characterized by a change in the attitude of the farmers participating in the program, while other indicators such as knowledge, skills, and actions do not characterize the effectiveness of communication. The success of the integrated farming systems program is only characterized by the creation of jobs and the development of farming intensification and extensification.The objectives of this research are: (1) analyze the relationship management of communication resources for extension with successful integrated farming systems and (2) designing a communications resource management model for extension of integrated farming system. To achieve these objectives, the study was conducted with survey design combined with the correlation approach. Determining the location of the study and determination of respondents using purposive, whereas data analysis using Structural Equation Modelling approach (SEM).The results showed: (1) communications resource for extension in the integrated farming system has not been managed in accordance with management functions and this is associated with less successful programs of integrated farming systems; (2) resource management model of communication for extension of integrated farming system is a structured scheme of action in managing communication resources in accordance with management functions